Technique for 3D shape reconstruction of spherical and aspheric surfaces using deflectometric principle - Novák P.; Novák J.; Mikš A. (EPJ Web of Conferences, 2013)
We provide a description and analysis of a deflectometric technique for 3D measurements of optically smooth surfaces. It is presented that a surface reconstruction problem leads to a theoretical description by a nonlinear partial differential equation. Then, a surface shape can be calculated by solution of a derived equation. The presented method is noncontact and no reference surface is needed as in interferometry.